2020
DOI: 10.3390/f11040432
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Genetic Diversity, Differentiation and Geographic Origin of Natural Provenances and Land Races of Casuarina equisetifolia Based on EST-SSR Markers

Abstract: Research Highlights: High variation of genetic diversity and differentiation among 27 seed sources within 14 natural provenances and 13 land race samples of Casuarina equisetifolia were found. High proportions of monoecious individuals may be present in some populations, as indicated by severe heterozytote deficiency and inbreeding found in many provenances and land races. The most probable origins of the land races were inferred according to the values of pairwise provenance differentiation and Nei’s genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that both environmental and genetic factors influence the potential of trees to produce fertile quality seeds whereby depending on the tree species, seed germination varied according to latitude, elevation, soil moisture, soil nutrient, temperature, type and density of plant cover, and degree of habitat disturbance of the site [49,50]. Location of seed at the time of maturity plays an important role in determining a forest tree's potential for seed quality and seed fertility [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that both environmental and genetic factors influence the potential of trees to produce fertile quality seeds whereby depending on the tree species, seed germination varied according to latitude, elevation, soil moisture, soil nutrient, temperature, type and density of plant cover, and degree of habitat disturbance of the site [49,50]. Location of seed at the time of maturity plays an important role in determining a forest tree's potential for seed quality and seed fertility [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…The mean Fis > 0 and the lower observed heterozygosity than the expected heterozygosity at species level indicates lack of heterozygosity in the populations of F. nilgerrensis. It was reported that lack of heterozygotes among the related individuals is due to either random mating with a restricted paternal pollen pool, or non-random mating (Zhang et al, 2020). Both a self-compatible breeding system and clonal propagation in F. nilgerrensis could cause the low outcrossing rates and heterozygosity.…”
Section: Discussionmentioning
confidence: 99%
“…Cone and seed production in other pines has also been shown to be positively influenced by larger basal areas [22,39]. Other factors such as stand density, climatic variations, and the morphological parameters of trees also influence their reproductive capacity [40][41][42]. It was reported that in some pines (for example Aleppo), sub-humid climate enhances cone production over semi-arid conditions.…”
Section: Tree Diameter and Cone Characteristicsmentioning
confidence: 99%